Pengembangan Perangkat Pembelajaran di PAUD Gemilang - Yuki Widiasari (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2017)
AbstractEarly childhood education curriculum must be appropriated with childrencharacter and the rule of government. This year every early childhoodeducation use 2013’s curriculum. In PAUD Gemilang this curriculum appliedtoo. Based on accreditation advise the institution have a problem in devicelearning because still applied the curriculum in a part of learning activity. Theproblem like: daily lesson plan and scientific evaluation. So, we improvedevice learning in order to appropriate.Keywords: device learning, early childhood education